"Misremembering the ACRS: economic imaginations and nuclear negotiations in the Middle East". Issue 3 (27th May 2021) - Taha, Hebatalla
ABSTRACT: This article examines the political economy of Arab-Israeli peacemaking in the first half of the 1990s, specifically the multilateral working group on Arms Control and Regional Security (ACRS). It focuses on the misplaced memorialization of the ACRS process as a lost opportunity for the establishment of a nuclear weapons free zone (NWFZ) in the Middle East, which has resulted in a continuous "return" to ACRS in policy discussions. The article contends that rather than producing mechanisms for disarmament, the ACRS process was part of a larger economic restructuring and served as a platform for militarized economic relations. Seeking to destabilize dominant repertoires on peacemaking in the Middle East, the article demonstrates the overlap between processes of nuclear entrenchment and economic imaginaries. It offers a deeper understanding of how the nuclear realm interacts with motifs of peace and prosperity.